Random terpolymer with a cost-effective monomer and comparable efficiency to PTB7-Th for bulk-heterojunction polymer solar cells. Issue 4 (14th December 2015) - Jiang, Tao; Yang, Jie; Tao, Youtian; Fan, Cong; Xue, Lingwei; Zhang, Zhiguo; Li, Hai; Li, Yongfang; Huang, Wei
Abstract : A new random terpolymer PTB7-Th-T2 was designed and synthesized for high performance PSCs by incorporating a significantly lower-cost 2, 2′-bithiophene monomer to the famous PTB7-Th skeleton. Abstract : A new random terpolymer PTB7-Th-T2 has been designed and synthesized by incorporating a significantly lower cost monomer, 2, 2′-bithiophen, for application as a donor material in polymer solar cells (PSCs). By replacing 25 mol% of extremely expensive 3-fluorothieno[3, 4- b ]thiophene-2-carboxylate monomer in the famous PTB7-Th by a >30-times lower cost bithiophene, the new terpolymer PTB7-Th-T2 shows a comparable HOMO energy level and increased absorption intensity in the wide wavelength range of 400–700 nm. In addition, in a polymer/PC71 BM blended film, the hole mobility has improved from 1.67 × 10 −4 for PTB7-Th to 2.49 × 10 −4 cm 2 V −1 s −1 for PTB7-Th-T2. A power conversion efficiency (PCE) of 7.05% has been achieved in a polymer bulk heterojunction photovoltaic device with the structure of ITO/PEDOT:PSS/PTB7-Th-T2:PC71 BM (1 : 1.5, w/w)/Ca/Al by using 3% of 1, 8-diiodooctane (DIO) as a solvent additive. Furthermore, through introducing an amino-substituted perylene diimide (PDIN) as the cathode interlayer, a high fill factor (FF) of 67.38% and PCE of 8.19% have been obtained; these values are higher than those of the control polymer PTB7-Th of 63.26% and 7.93%, respectively at the same device conditions.